1991
DOI: 10.1007/bf02470871
|View full text |Cite
|
Sign up to set email alerts
|

Renal function in experimentally induced acute pancreatitis in dogs: How it is affected by the nephrotoxic substance in pancreatic exudate from ascitic fluid

Abstract: Renal failure occurring in dogs during experimental acute pancreatitis and the effect on renal function of intravenous injections of ascitic fluid which accumulated during the acute pancreatitis were studied. Five hours after the induction of acute pancreatitis, the accumulation of 200 to 400 ml of ascitic fluid, and an elevation in hematocrit as well as a decreased mean arterial pressure were observed, which suggested hypovolemia due to plasma loss. At the same time, the renal blood flow, glomerular filtratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0
2

Year Published

1995
1995
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 11 publications
1
20
0
2
Order By: Relevance
“…Levy et al 21 concluded that renal failure in acute pancreatitis was only the result of systemic hypovolemia; however Satake et al 22 contradicted this by demonstrating the existence of nephrotoxic substance(s) other than vasoactive substances or proteases.…”
Section: Kidneymentioning
confidence: 97%
“…Levy et al 21 concluded that renal failure in acute pancreatitis was only the result of systemic hypovolemia; however Satake et al 22 contradicted this by demonstrating the existence of nephrotoxic substance(s) other than vasoactive substances or proteases.…”
Section: Kidneymentioning
confidence: 97%
“…Acute kidney injury (AKI) and pancreatitis can lead to similar clinical signs. In addition, these 2 conditions are common comorbidities, as AKI is a well‐documented cause of pancreatitis via ischemia and hypovolemia, and pancreatitis can lead to AKI via hypovolemia and cytokine‐induced ischemia and inflammation . As with other serological biomarkers of pancreatitis, it is plausible that decreased glomerular filtration rate (GFR), as seen with AKI, could result in Spec cPL increase secondary to decreased renal clearance, in the absence of pancreatitis.…”
mentioning
confidence: 99%
“…Pancreatitis-induced ascitic fluid obtained from the canine model of necrotizing pancreatitis had a lethal effect on rats when administered into their abdominal cavities [7]. It has also been reported that PAF from a canine pancreatitis model caused acute renal failure in healthy dogs, suggesting that the nephrotoxic substances may be present in PAF [8]. We recently demonstrated that PAF contains cytotoxic factors that induce apoptosis in Madin-Darby canine kidney (MDCK) cells [9].…”
Section: Introductionmentioning
confidence: 96%